Human Price Index of Lampung Province using Multiple Linear Analysis - Rohimatul Anwar; Mika Alvionita Sitinjak (Faculty of Engineering, Univesitas Sultan Ageng Tirtayasa, 2025)
This study aims to determine the effect of the number of poor people, average years of schooling, open unemployment rate, and per capita expenditure on the human development index in Lampung Province. The data used are secondary data sourced from the Central Statistics Agency of Lampung Province. The data used is cross-sectional data from 2023 by district/city in Lampung Province. The analysis used is a multiple regression analysis of cross-sectional data. The results obtained indicate that the average years of schooling and per capita expenditure significantly influence the human development index in Lampung Province. In addition, 98.8% of the human development index variables in Lampung Province can be explained simultaneously by the number of poor people, average years of schooling, open unemployment rate, and per capita expenditure.